2011
DOI: 10.4103/0022-3859.85207
|View full text |Cite
|
Sign up to set email alerts
|

A study of drug-drug interactions in cancer patients of a south Indian tertiary care teaching hospital

Abstract: Though there was not any life threatening interactions, the potential interactions were brought to the oncologist purview for ensuring patients safety and to avoid undesirable effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
26
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 18 publications
8
26
0
Order By: Relevance
“…Although, depending on the study center, these statistics were different, for example, in the study by Guastaldi et al., 17 the major interactions accounted for 14.1% of the total interactions. On the other hand, in our study, about 44.4% of detected DDIs are in the moderate category, which was approximately equal to another similar study, 18 and about 40.6% of DDIs classified as major. Some studies have also reported higher percentages, for example, Richelmann et al.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Although, depending on the study center, these statistics were different, for example, in the study by Guastaldi et al., 17 the major interactions accounted for 14.1% of the total interactions. On the other hand, in our study, about 44.4% of detected DDIs are in the moderate category, which was approximately equal to another similar study, 18 and about 40.6% of DDIs classified as major. Some studies have also reported higher percentages, for example, Richelmann et al.…”
Section: Discussionsupporting
confidence: 68%
“…1 The prevalence of potential drug interactions in adult oncology centers in 2009 6 was estimated to be between 12% and 63%, and this prevalence has been reported in some adult oncology centers at even higher ranges, ranging from 36% to 60%. 17,18…”
Section: Discussionmentioning
confidence: 99%
“…In the present study drug-drug interactions were observed to be 167 out of which 20% was major, 78% was moderate and 1% was minor, this does not differs greatly from the study carried out by Kannan et al,which projects reporting of 213 interactions out of which 9% was major, 56% was moderate and 33% minor respectively [22]. Further in the present study, among chemotherapeutic drugs, it was found that methotrexate was the most potentially interacting drug followed by cisplatin and doxorubicin.…”
Section: Discussionmentioning
confidence: 31%
“…[ 7 8 16 ] One study from South India has reported drug–drug interactions involving anticancer drugs but does not mention the error rate of the prescriptions studied. [ 17 ] However, in our study, all the drugs were given parenterally as part of a protocol and there were no clinically relevant drug interactions in any of the prescriptions.…”
Section: Discussionmentioning
confidence: 97%